Strategi Komunikasi Public Relations PT Gamelan Tour dalam Membangun Citra Positif - Ade Irmayanti; Iin Soraya; Cindya Yunita Pratiwi (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This study aims to analyze the Public Relations (PR) communication strategy used by PT Gamelan Tour in building the company's positive image. This research applies the Two-Way Symmetric Communication theory developed by James E. Grunig and Todd Hunt, which emphasizes the importance of reciprocal communication between the company and the public. Through this approach, PT Gamelan Tour aims to listen to customer complaints, provide clear explanations,and resolve issues in a transparent and effective manner. Additionally, this study discusses various relevant communicationmanagementmodels,including thetwo-way symmetric model, which helps the company maintain mutually beneficial relationships with its customers. The research methodology uses a qualitative approach, collecting data through in-depth interviews with key stakeholders at PT Gamelan Tour, including Vania Nefrela Regar (Public Relations), Reva Agustina (Ticketing &Hotel), and the company's customers. This study adopts four steps of Public Relations strategy, which include: (1) defining the problem/facts to identify existing issues, (2) planning and programming to formulate effective communication strategies, (3) taking action and communicating to implement the planned strategies, and (4) evaluating the program to assess the success of its implementation and its impact on the company's image. The research findingsindicate that effective communication strategies, whether in the form of feedback, direct communication, or mutual understanding, can improve the company's image and strengthen relationships with customers.This studyalsohighlightstheimportanceofthoroughcommunication planning and consistent implementation to achieve the company's goals in building positive relationships with the public.